Political Legitimacy and Democracy in Central Africa: A Look at Cameroon, Chad, the Central African Republic and Gabon - Formella, Collins Nkapnwo (Afrika Tanulmányok / Hungarian Journal of African Studies, 2021)
This paper offers evidence of the intrinsic relationship between political legitimacy and democracy and scrutinizes the factors that provoke a crisis of political legitimacy and democracy in Central Africa. It contends that there is a need for the reconceptualization of political legitimacy and democracy in Africa as the conventional lines between democracy and totalitarianism seem to be clouding. It then concludes that despite the fact that democratic foundations in the region suffer from daunting challenges, demands for democratization continues to grow, resulting in the need to pay close attention to state legitimacy to ensure a democratic consolidation.